EVALUATION OF CYCLIC ADENOSINE MONOPHOSPHATE AND NEUROTRANSMITTERS IN EXPERIMENTAL OBESITY: IMPACT OF BLACK PEPPER AND COFFEE AQUEOUS EXTRACTS - Fathy, Shadia; Latif, Yasmin Abdel; El-khayat, Zakaria; Moustafa, Maha; Farrag, Abdel Razik; Farahat, Aya (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study aims to evaluate the effect of black pepper and coffee extracts on chronic and acute experimental-induced obesity and energy homeostasis. Methods: Rats were divided into 10 groups including control, high-fat diet (HFD), triton, HFD+triton, black pepper+HFD, black pepper+HFD+triton, coffee+HFD, coffee+HFD+triton, mixture+HFD, and mixture+HFD+triton groups. Blood glucose, serum insulin, and insulin resistance were estimated. Body mass index, food efficiency intake, and body weight gain were calculated. Lipid profile, liver and kidney functions were measured, serum and brain cyclic adenosine monophosphate (cAMP) was estimated, and brain neurotransmitters were measured by high-performance liquid chromatography. Furthermore, histopathology of liver was performed. Results: Findings showed that blood glucose, insulin resistance, lipid profile, kidney and liver functions as well as brain cAMP and neurotransmitters were significantly increased, concomitant with a significant decrease in insulin resistance and serum cAMP in both HFD and triton-induced obesity groups compared to control. Conclusion: Supplementation with black pepper extract, coffee extract, and a mixture of both significantly improved these findings. In conclusion, black pepper and coffee extracts are overlooked as promising weight reduction and antihyperlipidemic agents. Keywords: Energy homeostasis, Obesity, Black pepper extract, Coffee extract, Cyclic adenosine monophosphate, Neurotransmitters.